The multiplicity and anisotropy of galactic satellite accretion - Shao, Shi; Grand, Robert J. J. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. We study the incidence of group and filamentary dwarf galaxy accretion into Milky Way (MW) mass haloes using two types of hydrodynamical simulations:
Gesehen am 08.02.2019